P695 Effectiveness and Safety of Combination Biologic or Small Molecule Therapy in Inflammatory Bowel Disease. (30th January 2023) - McShane, C; Varley, R; Fennessy, A; Campion, J; Ring, E; Kelly, O; Slattery, E; Doherty, G; McCarthy, J; Kevans, D
Abstract: Background: Biologic and small molecule therapies have revolutionised the treatment of inflammatory bowel disease (IBD). Despite these advances, there appears to be a therapeutic ceiling with single agent therapy with up to 50% of patients failing to achieve long term remission. Combination of two biologic therapies or a biologic therapy and small molecule agent, with differing mechanisms of action, has the potential to improve IBD therapy outcomes. Information on the effectiveness and safety of this treatment strategy in IBD remains limited. Methods: A retrospective, multicentre study was carried out at five Irish Academic Centres within the Initiative Network. Combination biologic or small molecule use was defined as concomitant use of two biologics or one biologic and small molecule therapy licenced or undergoing clinical trial assessment for treatment of IBD. Patients who had received combination therapy were identified from institutional databases. Review of clinical records was performed and demographic data collected. Combination therapy persistence was considered a proxy for successful therapy outcome. Adverse events were documented. P values < 0.05 were considered significant in analyses. Results: The study cohort included 85 patients; 70% Crohn's disease (CD), 30% ulcerative colitis (UC); median (IQR) number of prior biologic therapies 3 (2 – 3); median (IQR) study follow up 40.71 weeks (13.68 – 82.86). Further baseline characteristics are described in Figure 1. 97 combination therapy trials were undertaken in 85 patients. 13 different combination therapy regimes were utilised with ustekinumab & vedolizumab being the most common regimen. 76.5% (n=65 patients) remained on combination therapy at last follow up. Higher rates of combination therapy discontinuation (p=0.04) and shorter time to combination therapy discontinuation were observed in UC compared with with CD (HR 0.48 [95% CI 0.21-1.11], p<0.05). 3.1% of the study cohort developed a serious or opportunistic infection. No deaths or intensive care unit admissions occurred during study follow up. Conclusion: Combination therapy is an effective therapeutic strategy with an acceptable safety profile in refractory IBD patients. Randomised controlled trials are required to clearly define the role of combination therapy in the management of IBD.